Optogenetic‐induced sympathetic neuromodulation of brown adipose tissue thermogenesis. Issue 2 (23rd December 2019) - Lyons, Carey E.; Razzoli, Maria; Larson, Erin; Svedberg, Daniel; Frontini, Andrea; Cinti, Saverio; Vulchanova, Lucy; Sanders, Mark; Thomas, Mark; Bartolomucci, Alessandro
Abstract: The brown adipose tissue (BAT) is a thermogenic organ that plays a major role in energy balance, obesity, and diabetes due to the potent glucose and lipid clearance that fuels its thermogenesis, which is largely mediated via sympathetic nervous system activation. However, thus far there has been little experimental validation of the hypothesis that selective neuromodulation of the sympathetic nerves innervating the BAT is sufficient to elicit thermogenesis in mice. We generated mice expressing blue light‐activated channelrhodopsin‐2 (ChR2) in the sympathetic nerves innervating the BAT using two different strategies: injecting the BAT of C57Bl/6J mice with AAV6‐hSyn‐ChR2 (H134R)‐EYFP; crossbreeding tyrosine hydroxylase‐Cre mice with floxed‐stop ChR2‐EYFP mice. The nerves in the BAT expressing ChR2 were selectively stimulated with a blue LED light positioned underneath the fat pad of anesthetized mice, while the BAT and core temperatures were simultaneously recorded. Using immunohistochemistry we confirmed the selective expression of EYFP in TH positive nerves fibers. In addition, local optogenetic stimulation of the sympathetic nerves induced significant increase in the BAT temperature followed by an increase in core temperature in mice expressing ChR2, but not in the respective controls. The BAT activation was also paralleled by increased levels of pre‐UCP1 transcript. Our results demonstrate that local optogenetic stimulation of the sympathetic nerves is sufficient to elicit BAT and core thermogenesis, thus suggesting that peripheral neuromodulation has the potential to be exploited as an alternative to pharmacotherapies to elicit organ activation and thus ameliorate type 2 diabetes and/or obesity.